Crude glycerine in diets for piglets - Carvalho,Paulo Levi de Oliveira (2012)
Two experiments were carried out to determine the nutritional value and to evaluate performance of piglets fed two types of crude glycerine (CG), which were made from vegetable oil (CGS) and a mix of animal fat + % soybean oil (CGA). In experiment I, a digestibility assay was conducted using 32 crossbred piglets (19.20±1.52 kg). The experimental unit consisted of one pig, with a total of four experimental units per diet. The glycerine levels used in the digestibility assay were 4, 8, and 12% of the basal diet (corn + soybean based). The digestible (DE) and metabolizable energy (ME) values of glycerine were estimated by regression of DE and ME intake (kcal/kg) vs. glycerine intake (kg). The values (as-fed basis) of DE and ME (kcal/kg) obtained were: CGS = 5,070 and 4,556; CGA = 5,143 and 4,488, respectively. The results indicate that these two types of glycerine are a highly-available energy source for the feeding of piglets (15-30 kg). In experiment II, 90 piglets (BW = 15.18±0.67 to 30.28±1.68 kg), were allotted in a completely randomized design in 2 × 4 factorial arrangement, with of two types of crude glycerine (CGS and CGA) and four inclusion levels (3, 6, 9, and 12%). Five experimental units (pens with two pigs) were used for each level of crude glycerine, resulting in five replicates per treatment in the diet. Additionally, a control diet containing no glycerine (0%) was formulated. There was no interaction between levels of CG and types of crude glycerine, and the regression analysis indicates no effects of crude glycerine inclusion on performance and plasma variables. The results suggest that it is feasible to use up to 12% of both tyes of crude glycerine (obtained from soybean oil and mixed) in the diet for piglets without impairing performance, in addition to promoting a reduction of about 11% in the cost with feeding.